Unveiling the human fetal-maternal interface during the first trimester: biophysical knowledge and gaps - Masserdotti, Alice; Gasik, Michael; Grillari-Voglauer, Regina; Grillari, Johannes; Cargnoni, Anna; Chiodelli, Paola; Papait, Andrea; Magatti, Marta; Romoli, Jacopo; Ficai, Sara; Di Pietro, Lorena; Lattanzi, Wanda; et al. (Frontiers in Cell and Developmental Biology, 2024)
The intricate interplay between the developing placenta and fetal-maternal interactions is critical for pregnancy outcomes. Despite advancements, gaps persist in understanding biomechanics, transport processes, and blood circulation parameters, all of which are crucial for safe pregnancies. Moreover, the complexity of fetal-maternal interactions led to conflicting data and methodological variations. This review presents a comprehensive overview of current knowledge on fetal-maternal interface structures, with a particular focus on the first trimester. More in detail, the embryological development, structural characteristics, and physiological functions of placental chorionic plate and villi, fetal membranes and umbilical cord are discussed. Furthermore, a description of the main structures and features of maternal and fetal fluid dynamic exchanges is provided. However, ethical constraints and technological limitations pose still challenges to studying early placental development directly, which calls for sophisticated in vitro, microfluidic organotypic models for advancing our understanding. For this, knowledge about key in vivo parameters are necessary for their design. In this scenario, the integration of data from later gestational stages and mathematical/computational simulations have proven to be useful tools. Notwithstanding, further research into cellular and molecular mechanisms at the fetal-maternal interface is essential for enhancing prenatal care and improving maternal and fetal health outcomes.